2018
DOI: 10.1371/journal.pone.0203323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Carbapenem resistant Escherichia coli recovered from a tertiary hospital in Lebanon

Abstract: The emergence of carbapenem resistant Escherichia coli represents a serious public health concern. This study investigated the resistome, virulence, plasmids content and clonality of 27 carbapenem resistant E. coli isolated from 27 hospitalized patients at the American University of Beirut Medical Center (AUBMC) in Lebanon between 2012 and 2016. Whole-genome sequencing (WGS) data were used to identify resistance determinants. Multilocus sequence typing (MLST), pulsed field gel electrophoresis (PFGE), phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…In the carbapenemase-producers, the clinical isolates belonged to groups C (50%) and D (30%) while the environmental isolates were mainly groups B1, D, and A (Fig 6B ). A previous study showed that carbapenemase positive isolates distributed in groups A, D, B2, and B1 in descending order [44]. Only one isolate was unassigned to any phylogenetic group.…”
Section: Plos Onementioning
confidence: 90%
“…In the carbapenemase-producers, the clinical isolates belonged to groups C (50%) and D (30%) while the environmental isolates were mainly groups B1, D, and A (Fig 6B ). A previous study showed that carbapenemase positive isolates distributed in groups A, D, B2, and B1 in descending order [44]. Only one isolate was unassigned to any phylogenetic group.…”
Section: Plos Onementioning
confidence: 90%
“…Our finding agrees with studies conducted in Gambia, 41 Burkina Faso, 33 Ghana, 34 Saudi Arabia, 42 Israel, 43 Poland, 44 Sierra Leone, 45 and Lebanon. 46 This indicates ESBL-producing Enterobacteriaceae were rapidly emerging in developing and developed countries. In this study, ESBL-producing E. coli and K. pneumoniae were not only resistant to third-generation cephalosporins but also to other non-β lactams groups of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Strain EBJ003 belongs to ST405 and a different phylogenetic group D, suggesting distinct clonal dissemination from others. ST405 is a high-risk clone found in diverse hosts and it carries the bla NDM and bla CTX-M genes [35]. The bla NDM-5 -positive strains in this study were associated with ESBL/AmpC genes or CTX-M-types, demonstrating their ability to acquire different resistance genes.…”
Section: Discussionmentioning
confidence: 63%